Atypical energetic and kinetic course of excited-state intramolecular proton transfer (ESIPT) in room-temperature protic ionic liquids - Manna, Arpan; Sayed, Mhejabeen; Kumar, Anil; Pal, Haridas (Journal of Physical Chemistry B, 2014)
The excited-state intramolecular proton-transfer (ESIPT) process in 1,8-dihydroxyanthraquinone (18DHAQ) dye has been investigated in protic ionic liquid (PIL) solvents using photochemical measurements. The results demonstrate noteworthy modulations in both steady-state and time-resolved emission characteristics of excited normal (N*) and tautomeric (T*) forms of the dye. That the emission of T* increases unexpectedly upon increasing solvent viscosity indicates that subsequent to the initial forward ESIPT, there is also a relatively slower back ESIPT process involved for the excited dye. It is inferred that the propensity of this back ESIPT process is determined by the dynamics of the diffusive solvent relaxation, a process that is known to be strongly viscosity-dependent in ionic liquids. Evidence of both forward and back ESIPT for the dye has been obtained from femtosecond fluorescence up-conversion measurements. While an unusually fast forward ESIPT is clearly observed in all of the PILs studied, the uncommon back ESIPT process is distinctly indicated in PIL solvents having lower viscosities, certainly due to reasonably fast diffusive solvent relaxation in these solvents that causes a temporal modulation in the energies of the normal and tautomeric forms within a reasonably short time and thereby brings down the energy of N* compared to that of T*, triggering the back ESIPT process. Observation of solvent-viscosity-dependent back ESIPT is an intriguing finding for the present study as to the best of our knowledge, such a behavior has so far not been reported in the literature for the ESIPT reaction.